(untitled) (Scientific journal of the Fergana State University, 2024)
The article considers the effectiveness of developing creative cooperation skill of students based on the “Bit-lesson” technology according to the developed criteria. A comparative analysis of data from the intermediate stage of pedagogical research is given.